Miniature drilling machine prototype / Muhammad Zakiruddin Osman @ Mohd Nordin - Osman @ Mohd Nordin, Muhammad Zakiruddin (2022)
The project is about designing and fabricating a prototype on miniature drilling machine. The project will focus on show the design development of project using the SolidWorks software and the fabrication process of the project. Nowadays, the existing drilling machine is rather hard to use, heavy and taking up too many spaces because of big size. Consumers are sometimes clueless and lack of experience using the drilling machine. These customer desires a small, lightweight and easy-to-use drilling machine. In this project, research will be conducted mainly sourced from online database, websites and journals, about the title project that has been assigned to me. After that, 3 sketches will be made and then will be chosen as the best one and improvement will be added if there is some room for it. The best picked design is the one that satisfies the stated criterion and characteristic based on the early results obtained from Morphological and Pugh charts. Drilling materials such as aluminium, plastic wood, and steel will be tested on the drilling machine. The experiment's outcome will be obtained through observation.